Innovations in Stem Cell Transplantation 2013
DOI: 10.5772/53031
|View full text |Cite
|
Sign up to set email alerts
|

Tumorablative Allogeneic Hematopoietic Stem Cell Transplantation in the Treatment of High-Risk and Refractory Leukemia — New Concepts and Clinical Practice

Abstract: The substance of bone marrow transplantation is the organ transplantation. "ccurately, it is the grafting of hematopoietic and immunologic system. Comparing to the transplantation of solid organ, in the hematopoietic stem cell transplantation HSCT , the ill organ, id est. hematopoietic and immunology system, is ablated by high-dose chemotherapy and total body irradiation T"I conditioning regime . Thus, the normal hematopoietic stem cells could be engrafted and normal function of hematopoietic and immune system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, it is of great importance to seek a novel conditioning regimen to eliminate the leukemia as much as possible without increasing the TRM. According to the concept of tumorablative hematopoietic stem cell transplantation published previously [ 5 , 6 ], in this paper, we designed a TAC combined haplo-HSCT for children with hematologic malignancies in our center.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great importance to seek a novel conditioning regimen to eliminate the leukemia as much as possible without increasing the TRM. According to the concept of tumorablative hematopoietic stem cell transplantation published previously [ 5 , 6 ], in this paper, we designed a TAC combined haplo-HSCT for children with hematologic malignancies in our center.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary results have demonstrated that it reduced the relapse to about 20% in these patients. 4,5 Here we report the results of using TAHCT to treat the children patients with high-risk or relapsed hematologic malignancies.…”
mentioning
confidence: 99%
“…The further regimen was based on our previous protocol for adult HSCT. 5 Briefly, two regimens were included: regimen A, for patients who were older than 3 years or with extramedullary involvement: X (which is the effective anthracycline sought from the patient's chemotherapy history, for example, idarubicin 10 mg/m 2 .d, or aclarubicin 0.8 mg/kg.d, or mitoxantrone 10 mg/m 2 .d) (day − 14 to − 12), fludarabine 40 mg/m 2 .day (day − 13 to − 9), Ara-C 0.5-2.0 g/m 2 .12 h (day − 13 to − 9), rhG-CSF 5 ug/kg.day (day − 14 to − 9), teniposide (VM-26) 300 mg/m 2 .day (day − 8), TBI with 4.5 Gy/day (days − 7 to − 6), CY 40 mg/kg.day (days − 5 to − 4) and rabbit ATG (Fresenius) 5 mg/kg.day (days − 5 to − 2). The day of bone marrow (BM) and PBSC infusion was designated as day 1 and day 2.…”
mentioning
confidence: 99%
See 2 more Smart Citations